Assessment of the quality parameters of microwave-dried Ficus carica Linn leaves - Yilmaz, P.; Demirhan, E.; Ozbek, B. (SPRINGER HEIDELBERG, 2024)
Ficus carica Linn leaves represent a rich source of various bioactive compounds providing various features. Drying was inevitably preferred as a hopeful technique aiming to provide the availability of leaves and effective utilization of them in various fields. In the present study, the effects of microwave drying of dried Ficus carica L. leaves on optical, rehydration and bioactivity parameters were examined. The leaves were dried using a variety of microwave output power levels (180-900 W) with sample amounts (20-100 g). The effect of microwave drying on the optical properties of leaves was discussed based on the colour parameters (L, a, b) and total colour change (E). The final value of L, a and b and colour change (E) were respectively found as 37.600.49,-10.070.33, 16.08 +/- 0.18 and 10.19 +/- 0.062 for constant sample amount (20 g) at 900 W microwave output power level. On the other hand, the final value of L, a, b and colour change (E) were respectively found as 33.70 +/- 2.25,-8.79 +/- 0.87, 13.99 +/- 0.53 and 6.52 +/- 0.99 for the 100g sample amount at 360 W microwave output power level. The bioactive compounds of the leaves were handled in terms of total phenolic content (TPC) and scavenging activity (IC50) corresponding to the capability to scavenge 50% of radicals. The results explored that the TPC of fresh leaves, 46.77 +/- 0.39 (mg GAE/g DE), increased to 53.15 +/- 1.25 (mg GAE/g DE) by increasing microwave power intensity. Thereby, the IC50 value of fresh leaves, 768.77 +/- 1.58 (mu g/mL), decreased to 577.14 +/- 1.85 (mu g/mL). The kinetics and empirical models were successfully fitted to the experimental data obtained for microwave power intensity applied. Finally, it was concluded that the microwave technique could be safely applied for drying Ficus carica Linn leaves without detecting any undesirable change in the quality parameters monitored such as colour, rehydration and bioactive compounds.
Keywords: Ficus carica Linn leaves; Microwave drying; Colour change kinetics; Rehydration kinetics; Bioactive compounds; Mathematical modelling; COLOR-CHANGE KINETICS; ANTIOXIDANT ACTIVITY; DRYING KINETICS; POLYPHENOLS; PHENOLICS; EXTRACTS; ENERGY; PLANTS; Energy & Fuels; Engineering